The Effectiveness of SrVER-Based Learning Modules Integrated with Augmented Reality in Improving Students Health Literacy on the Circulatory System - Nikita Aulia Putri; Baiq Sri Handayani; Marosa Robiatul Adawiyah; Tri Ayu Lestari (Department of Mathematics and Science Education, Faculty of Teacher Training and Education, University of Mataram. Jurnal Pijar MIPA colaborates with Perkumpulan Pendidik IPA Indonesia Wilayah Nusa Tenggara Barat, 2026)
Biology, as a branch of natural science, plays an important role in providing students with an understanding of humans, the environment, and factors that influence health. This study aimed to determine the effectiveness of Screening, Visualization, Elaboration, and Reflection (SrVER)-based learning modules integrated with Augmented Reality (AR) in improving students’ health literacy in circulatory system learning at SMAN 3 Mataram. This study used a quantitative quasi-experimental design with a Non-Equivalent Control Group. The study involved 50 eleventh-grade students of SMAN 3 Mataram in the 2025/2026 academic year who studied the circulatory system material using a purposive sampling technique. Data were collected using multiple-choice questions. The data analyzed in this study were the N-Gain test and the Mann-Whitney test. The results of the prerequisite test showed that the data did not meet the assumptions of normality or homogeneity of variance; therefore, the analysis was conducted using the nonparametric Mann–Whitney U test on the N-gain score. The study found that the experimental class had an N-Gain of 0.8, in the high category, while the control class had an N-Gain of 0.3, in the low category. In addition, the Mann-Whitney test obtained an Asymp. Sig. (2-tailed) value of 0.000 <0.05, which means there is a significant difference in the post-test scores of the experimental and control classes. Thus, the null hypothesis (H0), which states that there is no effectiveness in using the SrVER-based learning module integrated with Augmented Reality (AR), is rejected. In contrast, the alternative hypothesis (Ha) is accepted. It can be said that using the SrVER-based learning module integrated with Augmented Reality (AR) to improve students' health literacy in the circulatory system material at SMAN 3 Mataram is effective.